Manganese Neurotoxicity as a Complication of Chronic Total Parenteral Nutrition - Alisha Khan; Jonathan Hingre; Amit S. Dhamoon (Case Reports in Neurological Medicine)
Manganese accumulation in the central nervous system creates clinical symptoms of cognitive dysfunction, behavioral changes, and movement disorders resembling Parkinson’s disease. Radiographic features of this rare clinical entity include symmetric T1 hyperintensities in the bilateral globus pallidi, with corresponding hypointensities on T2-weighted images. Total parenteral nutrition (TPN) is an increasingly used potentially lifesaving therapy for patients who cannot tolerate enteral nutrition. However, when used over a period of several weeks to months, its associated risks and complications carry significant morbidity and mortality. One of the more rare complications of TPN use is manganese toxicity. We provided care for a 38-year-old female on chronic TPN who presented to the hospital with Parkinsonian features, confusion, falls, and lethargy. MRI brain showed T1 hyperintensities in the bilateral globus pallidi, which were attributed to manganese toxicity from chronic TPN use. Supporting evidence for this rare entity included decreased signal intensity in the bilateral globus pallidi on T2-weighted images and T1 hyperintensities in the substantia nigra. With antifungal treatment and permanent cessation of TPN, her mentation and neurological symptoms began to improve within a week. Repeat MRI brain performed one month after discontinuation of TPN revealed improvement of the T1 hyperintensities in the bilateral globus pallidi. Our objective in presenting this case is to highlight manganese neurotoxicity as a rare complication of TPN in a patient without known hepatic dysfunction and to emphasize the importance of routinely monitoring patients for the possible adverse effects of chronic TPN. Our case is among the handful of published cases in which a patient without known liver dysfunction, which is the primary organ responsible for manganese elimination from the body, developed manganese neurotoxicity.